The civilisational history of the Malay archipelago: arguing for a new narrative - Bakar, Osman (ISTAC-IIUM Publications, 2020)
The book’s chapters attempt to provide a collective treatment of the theme of colonialism in the Malay Archipelago from the as yet little explored perspective of civilisational encounters. The centuries-long Western colonial presence in the Archipelago had generated both peaceful and violent quarters that were to prove consequential on the civilisational history of the region. The following thirteen chapters and Anwar Ibrahim’s keynote address attempt to present new insights into the nature and multi-dimensional character of these civilisational encounters and their significance for the life and thought of contemporary Malay Archipelago. The book has two main aims. First, to understand in civilizational terms the meaning and significance of selected major events that took place in the Malay Archipelago during the colonial period. Second, to understand the civilizational motives of the coming of European colonial powers to the Archipelago. Given these two aims that are basically concerned with civilizational ideas and issues, the science of which is still not widely understood,4 this book is thus essentially concerned with the civilizational history of the Archipelago. It is only appropriate, therefore, that we introduce this book with an explanation of the meaning of the word ‘civilization’ from which the adjective ‘civilizational’ comes. This explanation would help provide a theoretical framework for the wide-ranging discourse in the book.